The Degree of Commitment of Trainees to teaching Profession Ethics from the Points of View of the Cooperating Teachers with the Field Training Program at Al-al Bayt University (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
The study aimed at investigating the degree of commitment of the trainee students to teaching profession's ethics from the perspectives of the cooperating teachers at Al al-Bayt University: A 32- item questionnaire was built and distributed to (83) female classroom teachers. The study's main question stated as follows: what is the degree of commitment of trainee students' to teaching profession ethics from the cooperative teacher's points of view. The statistical treatments of the data showed a high commitment of trainee students to teaching profession's ethics in all six domains according to cooperative classroom teachers' points of view.